Core-shell iron oxide@stellate mesoporous silica for combined near-infrared photothermia and drug delivery: Influence of pH and surface chemistry - Adam, Alexandre (2022)
The chemical design of smart nanocarriers, providing in one nanoformulation combined anticancer therapies, still remains a challenge in the field of nanomedicine. Among nanomaterials, iron oxide-based core-shell nanostructures have been already studied for their intrinsic magnetic hyperthermia features that may be coupled with drug delivery. However, despite the great interest today for photo-induced hyperthermia, very few studies investigated the potential of such nanocarriers to combine photothermia and drug delivery. In this work, our aim was to design functional iron oxide@stellate mesoporous silica nanoparticles (denoted IO@STMS NPs) loaded with a drug and able to combine in a same formulation near-infrared (NIR) light induced photothermia with antitumor drug release. Herein, the NIR photothermal properties (SAR, specific absorption rates) of such nanomaterials were quantified for the first time as a function of the laser power and the NP amount. Aside the response to NIR light, the conditions to obtain very high drug loading (drug payloads up to 91 wt%) of the model antitumor drug doxorubicin (DOX) were optimized by varying different parameters, such as the NP surface chemistry (BARE (Si-OH), aminopropylsiloxane (APTES) and isobutyramide (IBAM)) and the pH of the drug impregnation aqueous solution. The drug release study of these core-shell systems in the presence or absence of NIR light demonstrated that the DOX release efficiency is mainly influenced by two parameters: surface chemistry (BARE ≥ IBAM ≥ APTES) and pH (pH 5.5 ≥ pH 6.5 ≥ pH 7.5). Furthermore, the temperature profiles under NIR light are found similar and independent from the pH range, the surface chemistry and the cycle number. Hence, the combination of local photothermia with lysosomal-like pH induced drug delivery (up to 40% release of the loaded drug) with these nanostructures could open the way towards new drug delivery nanoplatforms for nanomedecine applications.